Integrating traditional indigenous medicine and western biomedicine into health systems: a review of Nicaraguan health policies and miskitu health services. Issue 1 (December 2015) - Carrie, Heather; Mackey, Tim; Laird, Sloane N.
Abstract Throughout the world, indigenous peoples have advocated for the right to retain their cultural beliefs and traditional medicine practices. In 2007, the more than 370 million people representing 5000 distinct groups throughout the world received global recognition with the adoption of the United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP). UNDRIP Article 24 affirms the rights of indigenous peoples to their traditional medicines and health practices, and to all social and health services. Although not a legally binding agreement, UNDRIP encourages nation states to comply and implement measures to support and uphold its provisions. Within the context of indigenous health and human rights, Nicaragua serves as a unique case study for examining implementation of UNDRIP Article 24 provisions due to the changes in the Nicaraguan Constitution that strive for the overarching goal of affirming an equal right to health for all Nicaraguans and supporting the integration of traditional medicine and biomedicine at a national and regional level. To explore this subject further, we conducted a review of the policy impact of UNDRIP on health services accessible to the Miskitu indigenous peoples of the North Atlantic Autonomous Region (RAAN). We found that although measures to create therapeutic cooperation are woven into Nicaraguan health plans at the national and regional level, in practice, the delivery of integrated health services has been implemented with varying results. Our review suggests that the method of policy implementation and efforts to foster intercultural collaborative approaches involving respectful community engagement are important factors when attempting to assess the effectiveness of UNDRIP implementation into national health policy and promoting traditional medicine access. In response, more study and close monitoring of legislation that acts to implement or align with UNDRIP Article 24 is necessary to ensure adequate promotion and access to traditional medicines and health services for indigenous populations in Nicaragua and beyond.